2006
DOI: 10.1207/s15327914nc5501_10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional and Inflammatory Status of Advanced Colorectal Cancer Patients and Its Correlation With Survival

Abstract: The purpose of this study was to evaluate novel inflammatory and nutritional prognostic factors in patients with advanced colorectal cancer (ACRC). All ACRC patients attending the clinic for palliative treatment were eligible for study. Demographics, including performance status (PS), C-reactive protein (CRP), albumin (Alb), Glasgow prognostic score (GPS), weight, weight history, body mass index (BMI), and nutritional status using the patient-generated subjective global assessment (PGSGA), were collected and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 37 publications
9
109
0
4
Order By: Relevance
“…Recently, studies have demonstrated an important association between nutritional depletion and inflammation in cancer patients [4][5][6]14,16,17,[19][20][21][22] , including GIT tumors. Since cancer patients are in a constant state of inflammation, and considering the role of this systemic inflammation in progressive weight loss and muscle mass, cancer cachexia can be identified by the presence and alteration of certain inflammatory markers [5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have demonstrated an important association between nutritional depletion and inflammation in cancer patients [4][5][6]14,16,17,[19][20][21][22] , including GIT tumors. Since cancer patients are in a constant state of inflammation, and considering the role of this systemic inflammation in progressive weight loss and muscle mass, cancer cachexia can be identified by the presence and alteration of certain inflammatory markers [5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
“…However, as albumin concentration is affected by dehydration and malnutrition in canine patients, it would be difficult to be used it as an inflammatory marker in a clinical setting. Since inflammatory markers, including CRP and albumin concentrations have been used to score general conditions in human medicine recently [17,19], and these might also be used to assess the severity and prognosis of chronic diseases in canine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the CRP concentration along with WBC counts is clinically valuable as a screening test for new patients to detect inflammation. In human medicine, CRP has been reported to indicate the severity and prognosis of various diseases [9,10,16,17]. In veterinary medicine, it has been reported to indicate the response to treatment and prognosis in idiopathic polyarthritis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammatory response, as evidenced by the GPS, as a prognostic factor in patients with cancer [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%